Long-term outcomes of lung transplantation with ex vivo lung perfusion technique - Buttar, Sana N.; Schultz, Hans Henrik L.; Møller-Sørensen, Hasse; Perch, Michael; Petersen, Rene Horsleben; Møller, Christian H. (Frontiers in Transplantation, 2024)
Ex vivo lung perfusion (EVLP) has demonstrated encouraging short- and medium-term outcomes with limited data available on its long-term outcomes. This study assesses (1) EVLP long-term outcomes and (2) EVLP era-based sub-analysis in addition to secondary outcomes of recipients with EVLP-treated donor lungs compared with recipients of conventionally preserved donor lungs in unmatched and propensity score-matched cohorts. Double lung transplants performed between 1st January 2012 and 31st December 2021 were included. A total of 57 recipients received EVLP-treated lungs compared to 202 unmatched and 57 matched recipients who were subjected to non-EVLP-treated lungs. The EVLP group had a significantly lower mean PaO2/FiO2 ratio and significantly higher mean BMI than the non-EVLP group in the unmatched and matched cohorts. The proportion of smoking history in the unmatched cohort was significantly higher in the EVLP group, while a similar smoking history was demonstrated in the matched cohorts. No difference was demonstrated in overall freedom from death and retransplantation between the groups in the unmatched and matched cohorts (unmatched: hazard ratio (HR) 1.28, 95% confidence interval (CI) 0.79–2.07, P = 0.32; matched: HR 1.06, 95% CI 0.59–1.89). P = 0.89). In the unmatched cohort, overall freedom from chronic allograft dysfunction (CLAD) was significantly different between the groups (HR 1.64, 95% CI 1.07–2.52, P = 0.02); however, the cumulative CLAD incidence was similar (HR 0.72, 95% CI 0.48–1.1, P = 0.13). In the matched cohort, the overall freedom from CLAD (HR 1.69, 95% CI 0.97–2.95, P = 0.06) and cumulative CLAD incidence (HR 0.91, 95% CI 0.37–2.215, P = 0.83) were similar between the groups. The EVLP era sub-analysis of the unmatched cohort in 2012–2014 had a significantly higher cumulative CLAD incidence in the EVLP group; however, this was not demonstrated in the matched cohort. All secondary outcomes were similar between the groups in the unmatched and matched cohorts. In conclusion, transplantation of marginal donor lungs after EVLP evaluation is non-detrimental compared to conventionally preserved donor lungs in terms of mortality, retransplantation, cumulative CLAD incidence, and secondary outcomes. Although the unmatched EVLP era of 2012–2014 had a significantly higher cumulative CLAD incidence, no such finding was demonstrated in the matched cohort of the same era.